Pelatihan Pemanfaatan E-Commerce Bagi Peningkatan Mutu Sosial Tenaga Kerja dan Wanita di Kelurahan Rongtengah Sampang Madura - Ariesta Kartika Sari; Wanda Ramansyah; Puji Rahayu Ningsih; Medika Risnasari; Muchamad Arif; Sigit Dwi Saputro; Muhamad Afif Effindi (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
Small and Medium Enterprises (SME) has important role in economic growth. Along with the advance development of information technology emerging new tools for promoting product which can be used by SME. Through Public Service, the Department of Informatics Education Universitas Trunojoyo Madura sees potential economic development for SME for using tools such as e-commerce and Marketplace which is could guide to the enhancement of social quality of women and women labor, especially in Madura. Through the Public Service, it could be concluded further development of the attendees to use and promote their SME’s product.